KEANEKARAGAMAN GENETIK PADI LOKAL KALIMANTAN BARAT BERDASARKAN PENANDA ISOZIM - Siti Ifadatin; Elvi Rusmiyanto PW (Floribunda, 2006)
Siti Ifadatin& Elvi Rusmiyanto PW. 2006. Genetic Diversity of Local Rice from West KalimantanBased on Isozyme Markers. Floribunda 3(2): 38-43.- A study on the genetic diversity has been conducted on eight cultivars of the local rice from West Kalimantan, namely Pulut Hitam, Pulut Melor, Pulut Sangai, Ringkak Serandah, Kak Cundong, Belait, Remunai and Payah Temakan. Isozyme analysis by using three Esterase Enzyme System (EST), malic dehydrogenase (MDH) and peroxidase (PER) resulted in 13 loci where 9 loci (69%) of them are polymorphic loci. Of the Esterase Enzyme System (EST), there were 2 band patterns (EST1 and EST2), in malic dehydrogenase enzyme system (MDH) there were 4 band patterns, while in the system of peroxidase (PER) there were 8 enzyme band patterns. In the analysis with three enzyme systems, there was no band pattern which is specific for a certain cultivar, so that they can be distinguished one and the other. The result of the clustering analysis on 8 local rice cultivars fromWest Kalimantan showed that all of the 8 cultivars were grouped into one group with similarity level 66%. The genetic similarity and the phylogeny of the rice could not be separated based on the origin. The result of this cluster analysis showed  a tendency that Padi Pulut became one group which is different from non Padi Pulut.